Evaluation of stormwater runoff quality during monsoon and inter-monsoon seasons at tropical urban catchments. Issue 1 (2nd January 2016) - Chow, Ming Fai; Yusop, Zulkifli; Teo, Fang Yenn
ABSTRACT: Information on pollution level and the influence of a hydrologic regime on stormwater pollutant loading in tropical urban areas remains scarce. More local data is still required, as rainfall and runoff generation processes in tropical environment differ greatly from temperate regions. This study compares the stormwater runoff quality from urban catchments during monsoon and inter-monsoon seasons in the south of Peninsular Malaysia. Stormwater samples and flow rate data were collected from 38 storm events at three individual sites. Samples were analysed for total suspended solids (TSS), 5-day biochemical oxygen demand (BOD), chemical oxygen demand (COD), oil and grease (O&G), nitrate nitrogen (NO3 -N), ammoniacal nitrogen (NH3 -N), and total phosphorus (TP). Event mean concentration (EMC) was calculated for each pollutant for every monitored storm event at all study sites. The Mann–Whitney test was used to test for significance ( p  < 5%) in differences between the median EMCs of the pollutants. The results revealed that EMCs for stormwater runoff during the monsoon season were lower than that during the inter-monsoon season. Significant differences ( p  < .05) were found for EMC values for TSS, oil and grease, NH3 -N, and TP but not for BOD, COD, and NO3 -N. Stormwater pollutant loading of TSS, NH3 -N, and TP is higher during the inter-monsoon season while BOD, COD, and NO3 -N show higher loadings during the monsoon season. A better understanding of pollutant transport mechanisms will aid in formulating an effective stormwater management measures to control the urban stormwater pollution in the tropics.